(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aimed to study and analyse the effect of the promotion strategy with its elements: advertising, sales promotion, publicity, personal selling, and public relations on marketing performance, in a sample of industrial companies operating in Syria. The researcher distributed (300) questionnaires to a Convenience sample of individuals working in the branches of the following industrial companies under study: Toubi Plast Company for Plastic Industries in Damascus, Al-Reem Company for Plastic Products in Damascus Countryside, Al-Mateen International Company for Plastic Industries in Homs, and at all administrative levels (highest, middle, and lowest), (285) questionnaires were retrieved, and (5) questionnaires were excluded from them for not completing their data, and thus the number of questionnaires that were uploaded is (280) questionnaires. The researcher analysed the data using the statistical analysis program (SPSS 25). At the end of this research, the researcher reached a set of conclusions, the most important of which are: There is a significant effect of the promotion strategy with its five elements on the marketing performance of the Plastic Industrial Companies operating in Syria.